2009
DOI: 10.1042/bj20090922
|View full text |Cite
|
Sign up to set email alerts
|

Mutational analysis of human heat-shock transcription factor 1 reveals a regulatory role for oligomerization in DNA-binding specificity

Abstract: HSF (heat-shock transcription factor) trimers bind to the HSE (heat-shock element) regulatory sequence of target genes and regulate gene expression. A typical HSE consists of at least three contiguous inverted repeats of the 5-bp sequence nGAAn. Yeast HSF is able to recognize discontinuous HSEs that contain gaps in the array of the nGAAn sequence; however, hHSF1 (human HSF1) fails to recognize such sites in vitro, in yeast and in HeLa cells. In the present study, we isolated suppressors of the temperature-sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 53 publications
0
30
0
Order By: Relevance
“…Human HSF2, but not hHSF1, functionally complements a yeast hsf1Δ null strain, demonstrating that the hHSF2 isoform, which regulates developmentally controlled genes, retains its ancestral ability to control HSP genes (Liu et al 1997). hHSF1 can be made functionally competent in yeast through disruption of a coiled-coil intramolecular interaction domain or substitutions within the DBD, suggesting that human cells normally modulate these interactions to allow stress-induced activation Takemori et al 2009). Analysis of hHSF1 in the yeast system has also revealed that a loop region within the highly conserved DNA binding domain influences promoter recognition and trimerization (Ahn et al 2001).…”
Section: Global Analysis Of the Hsrmentioning
confidence: 99%
“…Human HSF2, but not hHSF1, functionally complements a yeast hsf1Δ null strain, demonstrating that the hHSF2 isoform, which regulates developmentally controlled genes, retains its ancestral ability to control HSP genes (Liu et al 1997). hHSF1 can be made functionally competent in yeast through disruption of a coiled-coil intramolecular interaction domain or substitutions within the DBD, suggesting that human cells normally modulate these interactions to allow stress-induced activation Takemori et al 2009). Analysis of hHSF1 in the yeast system has also revealed that a loop region within the highly conserved DNA binding domain influences promoter recognition and trimerization (Ahn et al 2001).…”
Section: Global Analysis Of the Hsrmentioning
confidence: 99%
“…1A). The RD harbors ϳ70% of the known HSF1 phosphorylation sites (33) and is capable of repressing HSF1 TAD in the absence of stress, rendering HSF1 inactive under normal conditions (22,27,28), and we therefore mutated the phosphorylation sites within this domain.…”
Section: Hsf1⌬ϳprd and Hsf1mentioning
confidence: 99%
“…A centrally located part of HSF1 is called the regulatory domain (RD). Deletion of the RD results in constitutive DNA-binding activity of HSF1 and induces expression of Hsps in the absence of stress (26)(27)(28). It has also been shown that the RD is self-sufficient in its heat-sensing capacity, since a chimeric transcription factor containing Gal4 DBD -HSF1 RD -VP16 TAD is repressed under normal conditions but is capable of activating transcription in response to stress (22).…”
mentioning
confidence: 99%
“…Enoki and Sakurai (2011) demonstrated that sequence differences in the HR-C domain of zebrafish HSF1a and HSF1c isoform affected oligomerization,which resulted in different binding affinities for discontinuous HSEs between the two isoforms. Recent studies of human and mice HSFs have demonstrated that different HSFs will recognize variations of HSE sequences, with HSF1 preferring a continuous inverted 5′nGAAn3′ repeat sequence while HSF2 and HSF4 are capable of binding to disordered versions of this sequence (Fujimoto et al 2008;Takemori et al 2009;Yamamoto et al 2009;Sakurai and Enoki 2010). In mouse lens tissue, 222 binding sites for HSF4 were identified, and of those binding sites, only six had perfect nGAAn repeats in the HSE sequences (Fujimoto et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Takemori et al 2009 demonstrated that specific amino acid regions of the hHSF1 DBD and HR-A/B domain regulate the ability of HSF1 to bind to discontinuous HSE sequences. Enoki and Sakurai (2011) demonstrated that sequence differences in the HR-C domain of zebrafish HSF1a and HSF1c isoform affected oligomerization,which resulted in different binding affinities for discontinuous HSEs between the two isoforms.…”
Section: Discussionmentioning
confidence: 99%